Price Volatility in the Manila Stock Exchange 1986-1993 - Aragon, Bienvenido M. (Philippine Management Review; Vol 4 (1993), 2016)
Share price volatility is an indicator of a stock market’s risk.  High volatility means high risk.  This, in turn, means that investors will demand high risk premiums, and, therefore, a higher cost of capital for firms.  This paper studies share price volatility in the Manila Stock Exchange (MSE) over the period January 1986 to December 1993.  It analyses the MSE Composite Index using two measures of volatility.  The study’s findings are:  One, there is no tendency for price volatility to increase.  In fact, volatility appears to have declined in recent years.  Two, sharp increases in volatility are transitory and can be easily traced to specific events, mostly political in nature.  Three, high volatility occurs not only during market crashes but have also coincided with bullish periods.  In other words, high volatility is not necessarily associated with a failing market.  Overall, the results appear to be good for capital market development.